(untitled) - Betsis, Andrew (Thành phố Hồ Chí Minh, 2014)
IELTS Candidates are guided step-by-step through the different tasks of the IELTS Reading section and at the same time increase their Vocabulary through engaging texts and plenty of vocabulary practice. It consists of 10 Units in which all the different tasks of the IELTS Reading section are dealt with
Keywords: Vocabulary,Reading comprenhention,English language,Từ vựng,Tiếng Anh,Đọc hiểu; Examinations,Kỳ thi